New findings and two new species of the genus Pallenopsis (Pycnogonida: Pallenopsidae) from the Southern Ocean - Esperanza Cano-Sánchez; Pablo J. López-González (Scientia Marina)
Pycnogonid specimens of the genus Pallenopsis collected during the Antarctic Polarstern XXIII/8 cruise (23 November 2006 to 30 January 2007) were studied. Seven species are recognized in this collection and two of them are proposed as new species: Pallenopsis tubercula n. sp., P. elephantensis n. sp., P. gracilis Cano-Sánchez and López-González, 2019, P. hodgsoni Gordon, 1938, P. macronyx Bouvier, 1911, P. spicata Hodgson, 1914 and P. aff. vanhoeffeni Hodgson, 1915. Pallenopsis gracilis is reported for the first time since its original description. The new species are described, illustrated and compared with their closest congeners, and their morphological variability is discussed. A cluster analysis (Euclidean distance) including our Pallenopsis specimens and the holotype of P. gracilis is carried out, based on 24 morphological characters. Finally, an updated key to the Southern Ocean species is presented.